- #1

- 14

- 0

If f(x) = 3x + 1

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

- Thread starter Aprilshowers
- Start date

- #1

- 14

- 0

If f(x) = 3x + 1

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

- #2

- 14

- 0

f(x) = 3x + 1

g(b) = (b^2 + 5b)^-1/2

Let b=f(x)=3x+1

Substitute 3x + 1 in for b:

g(b)=((3x+1)^2+5* (3x+1))^-.5

=(9x^2+6x+1+15x+5)^-.5

=(9x^2+21x+6)^-.5

g(f(x))= (9x^2+21x+6)^-.5

Please advise

- #3

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 956